Legalitas Hibah oleh Warga Negara Asing Atas Objek Tanah di Indonesia: Studi Kasus Putusan Pengadilan - Safira Ayudiatri; Akhmad Budi Cahyono (SIGn Jurnal Hukum, 2022)
This study aims to examine and analyze the legality of granting by Singaporean citizens to Indonesian citizens before the Notary Public of Singapore on land objects located in the territory of Indonesia based on Decision No. 912/Pdt.G/2018/PA.Jmb. In addition, this study further analyzes the laws and regulations that should apply in handling grants case based on international civil law. This research was conducted using a normative juridical approach with analytical descriptive specifications. The literature study was used to obtain the legal materials needed in this research. The collected legal material is then analyzed using qualitative data analysis methods with a statute and case approach. The results show that the legality of granting the object of land wills in Indonesia from former Indonesian citizens who have become foreign citizens to Indonesian citizens based on Decision No. 912/Pdt.G/2018/PA.Jmb is invalid and void by law. This case is contrary to Article 21 section (3) of Law No. 5 of 1960 and Article 37 section (1) of Government Regulation No. 24 of 1997. Based on the concept of International Civil Law, that action can be categorized as law smuggling, namely an act committed in a foreign country and recognized as legal in that foreign country. As for immovable objects, the general principle accepted in international civil law has stated that immovable objects in their status are based on the principle of lex situs or lex rei sitae. Therefore, it is recommended that every foreign citizen who has land rights or other property rights in Indonesia must relinquish the right of ownership within one year. The granting of land rights or property rights must be made in the grant agreement before the Land Deed Official of Indonesia. Furthermore, the registration of the transfer of land rights will be carried out at the National Land Agency of the Republic of Indonesia. Thus, land rights or property rights will get guarantees, protection, and legal certainty to avoid disputes in the future.